Performance of Bambara Nuts (Vigna subterranean L. Verdc) as Influenced by Genotypes and Weed Control Treatments in the Sudan Savanna Ecology, Nigeria - SHITTU, Emmanuel Abraham (Journal of Tropical Crop Science, 2025)
Global food security is threatened by population growth, climate change, and limited arable land. Bambara groundnut, an underutilized crop, faces challenges like low yields governed by weed competition and climate change stress. Given this, field trials were conducted to assess the performance of the Bambara nut as influenced by genotypes and weed control methods. The experiment comprised three genotypes of Bambara nut, “Yar Gombe”, “Duna Baki” and “Cream”, and eleven (11) weed control treatments, i.e. unweeded plots, hoe weeding at 3 and 6 weeks after sowing; application of imazethapyr at 2.0 kg a.i.ha-1; imazethapyr at 1.5 + bentazone at 1.5 kg a.i.ha-1; metolachlor at 2.0 kg a.i.ha-1; metolachlor at 1.5 + bentazone at 1.5 kg a.i.ha-1; pendimethalin at 2.0 kg a.i.ha-1; pendimethalin at 1.5 kg a.i.ha-1 + bentazone at 1.5 kg a.i.ha-1; pendimethalin at 1.5 kg a.i.ha-1 + supplementary hoe weeding; metolachlor at 1.5 kg a.i.ha-1+ supplementary hoe weeding; imazethapyr at 1.5 kg a.i.ha-1 + supplementary hoe weeding). The study was laid out in a split-plot design and replicated three times, with genotypes and weed control occupying the main and subplots. Findings revealed that plant height did not significantly differ due to genotypes, but “Duna Baki” had the widest canopy. Application of metolachlor at 1.5 kg a.i.ha-1 + hoe weeding conducted at 6 weeks after sowing, resulting in noticeably taller plants. The application of metolachlor and + imazethapyr each at 1.5 kg a.i.ha-1 + hoe weeding at 6 weeks after sowing produced the widest canopy cover. “Duna Baki” had the highest seed yield, whereas the “Yar Gombe” and “Duna Baki” had the heaviest seed. The phytosociological analysis identified Amaranthus spinosus, Eleusine indica, Cynodon dactylon, and Leucas martinicensis as the four most common weeds based on their importance value index (IVI). Consequently, farmers in the study area should be advised to use metolachlor and pendimethalin each at 1.5 kg a.i to increase yield and efficiently manage weeds.